Produção escrita de alunos surdos e consciência morfológica - Andréia Chagas Rocha Toffolo (2022)
This thesis aims to reflect, discuss and present work proposals with verbal morphology in order to collaborate with the discussion on the importance of morphological awareness of deaf students for the improvement of their writing. In order to identify the main difficulties in writing verbs, we analyzed texts produced by 17 profound deaf people enrolled in Elementary Public School in the state of Minas Gerais. We performed a qualitative and quantitative analysis of the data. The main difficulties identified in the writing of verbs were: (1) mistakes in verbal inflection; (2) verb phrase; (3) absence of verbs; and (4) inappropriate verb usage. After identifying such deviations, we hypothesize that they arise mainly from (1) the way deaf people perceive and process the Portuguese Language (PL), being fundamentally visual, without the support of a phonological lexicon to help them at the time of writing; (2) lack of knowledge or lack of mastery of vocabulary and aspects of PL related to verbal inflection; and (3) the transfer of knowledge from Brazilian Sign Language (Libras) as a first language (L1) to writing Portuguese as a second language (L2). We think, therefore, of the need to contemplate morphological awareness, considering Libras and with the support of visual resources. Based on the most recurrent mistakes presented on this thesis, we developed proposals for practices in six units that cover the themes: (1) Persons of the Verb and Referencing in Discourse; (2) Verbs in the Infinitive; (3) Verbs in the Present tense; (4) Verbs in the Past; (5) Verb Phrases, and (6) Irregular Verbs. We base our proposals on the statistical theory of Integration of Multiple Patterns – IMP (TREIMAN, 2018) – which postulates that learning to write takes into account the frequency of events, their combinations and the circumstances in which they occur, developing a kind of “ mental statistics”, and, from the perspective of visual literacy, in which the teaching of visual aspects of writing is prioritized in favor of orality (GESUELI; MOURA, 2006; LEBEDEFF, 2010; TAVEIRA; ROSADO, 2013; FARIA-NASCIMENTO, et al., 2021). The proposed practices sought to guide the learning in a conscious and intentional way (CLEEREMANS, 1993), with the presentation of rules and morphological generalizations aimed at the development of morphological awareness skills, with a view to promoting a reflection on the morphemes that form verbs, increasing vocabulary comprehension and, consequently, promoting improvements in spelling (NUNES et al., 2010; TRUSSELL et al., 2017). We believe that it is essential that the deaf learner is inserted into meaningful teaching practices, using strategies that direct their attention to details of linguistic forms, present in L2, in particular, to those forms that were not acquired due to lack of an auditory input. We also point out that there is a need for better knowledge of the writing of the deaf so that specific and targeted activities can be produced with a view to assisting them in this process of appropriation of the writing of the Portuguese Language, which is so important for their social and academic insertion.